A Move-based Analysis of illocutionary Speech Acts in American Presidential War Rhetoric - HUMMADI, ALI SALMAN; MAT SAID , SERIAZNITA BINTI (International Journal of Psychosocial Rehabilitation, 2020)
Presidential war discourse in particular is commonly investigated through the use of critical discourse analysis tools. Seldom attempts have been carried out to study this type of rhetoric in view of a move based analysis of illocutionary speech acts. Being a genre in its own, the particulars of the presidential war rhetoric are framed into narrated events within conventional move-structures realized by illocutionary speech acts indicative of the communicative function of each move to justify American present course of military action. After the study shows that American presidents organize their war rhetoric, in terms of a succession of seven cognitive move-structures, the study mainly focuses on investigating the types of illocutionary speech acts performed in each exigence or rhetorical move and identifying how they behave in realizing the local communicative function of the moves which, in turn, contribute to the communicative purpose of the genre as a whole. These exigences or move-structures are established by the events, the needs of the audience, and the purposes of the president. The results of the study show that the types of illocutionary speech acts performed by presidents vary in terms of the way these acts respond to the exigences that call them forth (the rhetorical moves in the present study).